South African twelfth grade students’ conceptions regarding Electrochemistry - Kwaku Darko Amponsah (Intelektual Pustaka Media Utama, 2020)
This current study explored twelfth-grade students' conceptions regarding electrochemistry in the Ximhungwe circuit of the Bohlabela district in the Mpumalanga province of South Africa. The sequential explanatory design was used to gather and analyse quantitative data first before gathering and analysing qualitative data for the current study. In the 2015 academic year, a sample of 10 twelfth-grade physical sciences students from four intact science public high schools was conveniently selected to participate in the current study after analysing the results of the quantitative data. Thirteen questions in which at least 30% of students showed misconceptions were selected for the interview. The result of the interviews indicated that students in the experimental group (EG) had more accurate concepts related to the function of the salt bridge in galvanic cells and the concept of electrical neutrality of anodes and cathodes compared to the control group (CG). Both the EG and the CG had the same viewpoints related to oxidation numbers, electrode potential, Emf calculations, and the identity of electrodes in galvanic cells and electrolytic cells when the placement of the electrodes was altered. However, students in both groups had limited knowledge about electrolytic cells, although the CG had more limited comprehension. It was recommended that educators teach concepts as much as they teach algorithms.